Achievements and Challenges of Integrated River Basin Management - Komatina, Dejan (IntechOpen, 2018)
Integrated river basin management is an approach focusing on the development and management of land and water resources in a coordinated manner with the primary aim to ensure society development, which is well balanced from the environmental, economic, and social points of view. It is a complex approach, including all aspects of water resource management (water and aquatic ecosystem protection, disaster management, and water use) and covering a wide range of disciplines (e.g., hydrology, ecology, environmental management, and economy), cross-cutting issues (climate change, data sharing, and stakeholder involvement), and approaches (river basin management plans preparation, water-food-energy-ecosystems nexus assessment, science-policy integration, and transboundary cooperation). This book provides a comprehensive overview of achievements and challenges associated with the implementation of the approach throughout the world.